2008
DOI: 10.1093/nar/gkn1004
|View full text |Cite
|
Sign up to set email alerts
|

Cellular versus viral microRNAs in host-virus interaction

Abstract: MicroRNAs (miRNAs) mark a new paradigm of RNA-directed gene expression regulation in a wide spectrum of biological systems. These small non-coding RNAs can contribute to the repertoire of host-pathogen interactions during viral infection. This interplay has important consequences, both for the virus and the host. There have been reported evidences of host-cellular miRNAs modulating the expression of various viral genes, thereby playing a pivotal role in the host–pathogen interaction network. In the hide-and-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
151
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(152 citation statements)
references
References 120 publications
(169 reference statements)
1
151
0
Order By: Relevance
“…Although miRNAs occupy negligible genomic space, they can modulate diverse biological functions. Consequently, after the discovery of the first viral miRNA in 2004 (Pfeffer et al, 2004), several other viruses were found to encode multiple miRNAs from their genome (Ghosh et al, 2009;Kincaid & Sullivan, 2012;Pfeffer et al, 2005;Sullivan et al, 2005). miRBase release 20 housed nearly 500 viral miRNAs, with the majority being encoded by DNA viruses (Griffiths-Jones, 2004;Griffiths-Jones et al, 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Although miRNAs occupy negligible genomic space, they can modulate diverse biological functions. Consequently, after the discovery of the first viral miRNA in 2004 (Pfeffer et al, 2004), several other viruses were found to encode multiple miRNAs from their genome (Ghosh et al, 2009;Kincaid & Sullivan, 2012;Pfeffer et al, 2005;Sullivan et al, 2005). miRBase release 20 housed nearly 500 viral miRNAs, with the majority being encoded by DNA viruses (Griffiths-Jones, 2004;Griffiths-Jones et al, 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, HBV has evolved to use viral miRNAs as a means to regulate its own gene expression [35] . miRNAs from the host cells may play a role in building up direct or indirect effect in regulating viral genes [34,36,37] . Hepatitis C virus (HCV) is an enveloped RNA virus of the Flavivirus family, which is capable of causing both acute and chronic hepatitis in humans by infecting liver cells.…”
Section: Mirnas and Liver Diseases Mirnas And Viral Hepatitismentioning
confidence: 99%
“…[27][28][29] Host cellular miRNAs modulate viral gene expression and viral gene silencing mechanisms enable host immune evasion and can exploit the cellular miRNA pathway to their own advantage. 30 Work on wild-type viruses has shown that viral miRNAs inhibit aspects of the host-adaptive immune response, including antigen presentation, the innate immune response including induction of apoptosis or the interferon system. 28 Because most of the modified viruses used for gene therapy have genes encoding miRNAs deleted, this may be of importance in preventing them from evading the immune response and therefore leaving them more susceptible to immune attack, unlike their wild-type counterparts.…”
Section: Current Understanding Of the Immune Responses In The Cnsmentioning
confidence: 99%